Pengembangan Perangkat Problem Based Learning (PBL) dalam Pembelajaran Matematika di SMA - Suci Mahya Sari; Rahmah Johar; Hajidin Hajidin (Universitas Syiah Kuala, 2016)
Problem Based Learning, PBL, is one of concept learning to apply real life concept and present problem in the beginning of learning. In the textbook, the topic of learning not suitable with daily activities of students and a teacher not understood what he or she taught to their student. In fact, the case will bring a situation which pupils not interested with mathematics because they did not learn about what they need. Based on the case, it created a development students book, teachers book, and student worksheet. They presented problems in student life. This research has purposed to generated the mathematics learning with PBL models are valid and practical. In study, the method was used a development research, namely Dick model and Carey model. The learning PBL consists of the teachers book, student worksheet, lesson plan, and achievement test. Based on development, it shown that validation learning tools were resulted the overall validation of learning illustrated validity criteria was very valid, validation of test result was valid, and validation of question was valid. Furthermore, learning tool developed was practical category, it based on experiment in in SMA Negeri 8 Banda Aceh and students of class X which has very good of activities percentage, learning process very good by teacher observation, and test result on worksheet was very good. The assignment of student and teacher to the learning tool show good criteria, and score of students test have reached an average by 76.1.The conclusion, in this research, shown that the PBL learning tool developed which fulfill valid categorize and practical